Pengaruh Word of Mouth dan Content Marketing Terhadap Repurchase Intention melalui Consumer Satisfaction sebagai Variabel Intervening - Husna, Indah Zulfatul; Purwanto, Edy (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
In marketing, companies are required to be able to market the products they produce, so that consumers are interested in making purchases. This research aims to research and analyze the influence word of mouth And content marketing to repurchase intention with consumer satisfaction as an intervening variable. This type of research is quantitative with the population, namely consumers who have made purchases at Seblak Piscok Montok, and the sample in this study was 128 people. The results of this research show that word of mouth And content marketing influence on consumer satisfaction. Word of mouth proven to have an effect on repurchase intention. content marketing has no effect on repurchase intention. Consumer satisfaction influence on repurchase intention. Consumer satisfaction proven to mediate influence word of mouth to repurchase intention as well as consumer satisfaction proven to mediate influence content marketing to repurchase intention.